Dietary polyphenols reduced the allergenicity of β-lactoglobulin via non-covalent interactions: a study on the structure-allergenicity relationship - Chi Zhang; Qiaozhi Zhang; Huatao Li; Zhouzhou Cheng; Shiyu Fan; Hujun Xie; Zhongshan Gao; Yan Zhang; Linglin Fu (Food Science and Human Wellness)
Studies showed that complexation of polyphenols with milk allergens reduced their immunogenic potential. However, the relationship between structures of polyphenols and their hypoallergenic effects on milk allergens in association with physiological and conformational changes of the complexes remain unclear. In this study, polyphenols from eight botanical sources were extracted to prepare non-covalent complexes with β-lactoglobulin (β-LG), a major allergen in milk. The dominant phenolic compounds bound to β-LG with a diminished allergenicity were identified to investigate their respective role on the structural and allergenic properties of β-LG. Extracts from Vaccinium fruits and black soybeans were found to have great inhibitory effects on the IgE-and IgG-binding abilities of β-LG. Among the fourteen structure-related phenolic compounds, flavonoids and tannins with larger MWs and multi-hydroxyl substituents, notably rutin, EGCG, and ellagitannins were more potent to elicit changes on the conformational structures of β-LG to decrease the allergenicity of complexed β-LG. Correlation analysis further demonstrated that a destabilized secondary structure and protein depolymerization caused by polyphenol-binding were closely related to the allergenicity property of formed complexes. This study provides insights into the understanding of structure-allergenicity relationship of β-LG-polyphenol interactions and would benefit the development of polyphenol-fortified matrices with hypoallergenic potential.